The Salix SmSPR1 Involved in Light-Regulated Cell Expansion by Modulating Microtubule Arrangement - Xiaoxia, Liu; Zhang, Jianguo; Jinkai, Sui; Ying, Luo; Guodong, Rao (Frontiers in Cell and Developmental Biology, 2019)
Light signaling and cortical microtubule (MT) arrays are essential to the anisotropic growth of plant cells. Microtubule-associated proteins (MAPs) function as regulators that mediate plant cell expansion or elongation by altering the arrangements of the MT arrays. However, current understanding of the molecular mechanism of MAPs in relation to light to regulate cell expansion or elongation is limited. Here, we show that the microtubule-associated protein SPR1 is involved in light-regulated directional cell expansion by modulating microtubule arrangement. Overexpression of SmSPR1 in Arabidopsis results in right-handed helical orientation of hypocotyls in dark-grown etiolated seedlings, whereas the phenotype of transgenic plants was indistinguishable from those of wild-type plants under light conditions. Phenotypic characterization of the transgenic plants showed reduced anisotropic growth and left-handed helical MT arrays in etiolated hypocotyl cells. Protein interaction assays revealed that SPR1, CSN5A (subunits of COP9 signalosome, a negative regulator of photomorphogenesis), and ELONGATED HYPOCOTYL 5 (HY5, a transcription factor that promotes photomorphogenesis) interacted with each other in vivo. The phenotype of Arabidopsis AtSPR1-overexpressing transgenic lines was similar to that of SmSPR1-overexpressing transgenic plants, and overexpression of Salix SmSPR1 can rescue the spr1 mutant phenotype, thereby revealing the function of SPR1 in plants.